PENDEKATAN PSIKOSOSIAL-EKONOMI MELALUI DUKUNGAN PSIKOLOGIS AWAL DAN DIGITAL ENTREPRENEURSHIP PADA ANAK PANTI - Raditya, Dewi Ilma Antawati; Khosianah, Fety; Bambang Raditya Purnomo (UNIVERSITAS PGRI MADIUN, 2026)
Abstract. This community service program was conducted at Muhammadiyah Orphanage Gersikan Surabaya with a unique integrative approach that combines psychosocial and economic empowerment. The main problems faced by the partner included the lack of caregivers’ capacity in providing Psychological First Aid (PFA), low awareness of sexual violence prevention among students, and limited digital entrepreneurship skills needed for independent living after leaving the orphanage. The aim of this community service activity is to increase the capacity of caregivers to provide initial psychological support and increase the independence and economic readiness of orphaned children through digital entrepreneurship training and education on preventing sexual violence. The program consisted of three training activities: (1) PFA for caregivers, (2) sexual violence prevention training for students from elementary to university level, and (3) digital entrepreneurship training for students from junior high to university level. The results showed significant improvements: caregivers were able to apply basic PFA skills, students improved their awareness of self-protection and reporting mechanisms, and adolescents successfully produced digital marketing content and used online marketplaces for product sales simulations. The integration of psychological support with digital entrepreneurship training represents a novel approach to orphanage empowerment, fostering not only psychological resilience but also economic independence. Abstrak. Program pengabdian masyarakat ini dilaksanakan di Panti Asuhan Muhammadiyah Gersikan Surabaya dengan pendekatan unik berupa integrasi aspek psikososial dan ekonomi. Permasalahan utama mitra meliputi rendahnya kapasitas pengasuh dalam memberikan dukungan psikologis awal, rendahnya kesadaran santri terhadap pencegahan kekerasan seksual, serta terbatasnya keterampilan kewirausahaan digital yang relevan dengan kebutuhan kemandirian pasca-panti. Tujuan kegiatan pengabdian kepada masyarakat ini adalah meningkatkan kapasitas pengasuh dalam memberikan dukungan psikologis awal serta meningkatkan kemandirian dan kesiapan ekonomi anak panti melalui pelatihan kewirausahaan digital dan edukasi pencegahan kekerasan seksual. Program ini merealisasikan tiga bentuk pelatihan, yaitu: (1) Dukungan Psikologis Awal (DPA) untuk pengasuh, (2) pencegahan kekerasan seksual untuk santri mulai SD hingga perguruan tinggi, dan (3) kewirausahaan digital untuk santri SMP hingga perguruan tinggi. Hasil kegiatan menunjukkan peningkatan signifikan: pengasuh mampu menerapkan keterampilan dasar DPA, santri memahami perlindungan diri dan strategi pelaporan kasus kekerasan seksual, serta santri remaja mampu menghasilkan konten promosi digital dan memanfaatkan marketplace untuk simulasi penjualan produk. Integrasi dukungan psikologis dengan pelatihan digital entrepreneurship ini menjadi pendekatan baru dalam pemberdayaan anak panti yang tidak hanya menumbuhkan resiliensi psikologis tetapi juga meningkatkan kemandirian ekonomi.